Uma aquisição, uma nova cultura e um velho clima - Albuquerque, Marco Antônio Fontoura de (2002)
The purpose of this study was evaluate the efficiency and effectiveness of being strategic tool, applied to Castrol Brazil, to make possible to conduct the company towards the needed changes facing the scenery that it vvas going through of being acquired by British Petroleum. Besides contributing to the administration of this changing process, providing favorable atmosphere to motivation, synergy and mobilization of ali employees facing the results maintenance, also contributed to the implementation of its sustainable development policy. via a solid culture of corporative social responsibility. Also, it doesn't present itself as directive and exclusive tool, only applicable to the described reality. but adaptable and that could be used in several merger and acquisition processes, enabling the companies to be acquired the cleaned understanding of the mission and the corporative vision. the faster incorporation of the new values and the acquisition of the best results in short and médium terms. The methodology used was descriptive, explanatory and applied. making use of documental, bibliographical means, study of cases and mainly participative. by total interaction of the researcher in the context of this study